Quest for novel chemical entities through incorporation of silicon in drug scaffolds - Ramesh, Remya; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
In order to optimize a lead molecule for further development, bioisosteric replacements are generally adopted as one of the strategies. Silicon appears to be the right choice as a carbon isostere because of the similarity in chemical properties. Silicon can be strategically introduced in a molecule to modulate its druglike properties, providing medicinal chemists with an unconventional strategy for replacing a carbon atom. Silicon can also be introduced to replace other heteroatoms and can act as a surrogate of functional groups such as olefin and amide as well. The present Perspective focuses on the opportunities that silicon incorporation offers in drug discovery, with an emphasis on case studies where introduction of silicon has created a benefit over its analog. We have tried to highlight all the recent developments in the field and briefly discuss the challenges associated with them.